Quantifying, Projecting, and Addressing India's Hidden Hunger - Ritchie, Hannah; Reay, David S.; Higgins, Peter (Frontiers in Sustainable Food Systems, 2018)
It is estimated that more than two billion people suffer from 'hidden hunger' (micronutrient malnutrition) globally, with nearly half living in India. Despite being highlighted as one the most cost-effective investments for human development, progress on addressing micronutrient deficiencies (MiND) has been slowing. The severe social, health and economic costs of MiND in India should make it a top priority for domestic governance and international donors alike. This study, for the first time, maps food system pathways from crop production through to household-level food availability, for a range of key vitamins, minerals and amino acids. Results suggest widespread (>80% total Indian population) risk of deficiencies in calcium, vitamin A, B12, folate, in addition to lysine limitation, with more localised deficiencies (<25% population) in iron, zinc, and vitamin B6. These deficiencies are the result of a combination of a monotonous cereal-dominated diet lacking in diversity, and overall insufficient food intake. This approach also allowed for 'MiND by micronutrient' scenario analysis to 2030, to identify potential intervention points in the food system and the capacity of these interventions to address deficiency. Scenario analysis to 2030 and 2050 indicates that, although increased availability of animal-based products, reduction of supply chain losses, and close to maximum (90%) attainable yields could make some contribution to addressing Indian MiND, additional intervention strategies will be essential. Recommendations for intervention in the short (urgent), near-term (2030) and long-term (2050) have been formulated based on this analysis.